Influence of environmental oxygen pressure variation in sea level native guinea pigs bone formation - Aguirre Siancas, Elías Ernesto (2014)
Introduction: Hypoxia characterizes initially injured tissue; variation in oxygen available determines the appearance of molecules involved in bone repair. Objectives: To determine if environmental oxygen pressure variation influences bone formation following osteotomy in sea level native guinea pigs. Design: Experimental. Setting: Faculty of Dentistry, Universidad Nacional Mayor de San Marcos, Lima, Peru, and Tropical and High Altitude Research Veterinary Institute, Mantaro, Peru. Biological material: Guinea pigs. Interventions: Five groups of 10 guinea pigs each were formed: one without osteotomy (control group), and four experimental groups: sea 15 days and sea 30 days (exposed to environmental PO2 157 mmHg), high altitude 15 days and high altitude 30 days (exposed to environmental PO2 107 mmHg). Main outcome measures: Osteocytes count. Results: The 15 days sea group had lower number of osteocytes compared with the 15 days high altitude group (63 180 vs. 80 310, p<0.05). The 30 days sea group had also lower number of osteocytes compared with the 30 days high altitude group (160 640 vs. 167 370, p<0.05). Conclusions: The lower environmental oxygen pressure favored higher bone formation in sea level native guinea pigs.